Community-based local capacities for peace in pastoralist areas : the case of Isiolo District - Kenya - Kimani, M. J. (Irish School of Ecumenics, 2007)
There exists a conventional contention, albeit largely anecdotal, that pastoralist areas, for all intents and purposes, are “a lost cause”. There is a relentless media bombardment portraying communities forever embroiled in violent and deadly conflict, inaccessible, ravaged by drought and famine and shadowed by hunger and death of people and their livestock. TV footage portrays nothing but heavily armed marauding gangs of raiders wreaking havoc sometimes on their own people, but mostly on neighboring communities in violent livestock raids. The colonial governments started painting a picture that the post-colonial governments have all been too eager to embrace thus, giving credence to a myth of a community in perpetual war with itself However, this research study hypothesized that this myth has no foundation.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin